KOMPLEKSITAS SINTAKSIS BAHASA INDONESIA PADA ANAK DENGAN GANGGUAN SPEKTRUM AUTISME DI SLB BHAKTI LUHUR JAKARTA - Dwi Septiani; Siti Zahra (Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to examine the syntactic complexity of Indonesian language in a 9-year-old child with Autism Spectrum Disorder (ASD) at SLB Bhakti Luhur, Jakarta. Using a qualitative-exploratory case study approach combined with Mean Length of Utterance (MLU) analysis, the study analyzed 84 spontaneous utterances from a subject identified by initials HS. Data were collected through participant observation, audio recordings, and interviews with support teachers. Findings indicate a dominance of declarative (50%) and imperative (19%) sentences, with an average MLU value of 4.62, reflecting a syntactic developmental level equivalent to children aged 4–6 years. Despite a gap between chronological age and syntactic age, the subject demonstrates functional basic verbal communication. This study provides empirical insights into the dynamics of syntactic acquisition in autistic children and lays an initial foundation for targeted linguistic interventions in inclusive educational settings in Indonesia.